Easy access to pharmaceutically relevant heterocycles by catalytic reactions involving alpha-imino gold carbene intermediates - Zhao, Ximei; Rudolph, Matthias; Asiri, Abdullah M.; Hashmi, A. Stephen K. (Frontiers of chemical science and engineering, 2020)
This review summarizes recent advances in the field of gold-catalyzed synthesis of pharmaceutically relevant aza-heterocycles via in situ generated alpha-imino gold carbene complexes as intermediates.